In the shadow of Perón : Juan Atilio Bramuglia and the second line of Argentina's populist movement - Rein, Raanan, 1960- (Stanford University Press., 2008)
Populism has been one of the most important phenomena in the political and social history of Latin America. This book challenges several commonly held assumptions about the nature of populism and the relations between the charismatic leader and the popular masses. Devoted to the second line of Peronist leadership in Argentina from the 1940s onwards, it focusses on the figure of Juan Atilio Bramuglia, who tried to offer an alternative path for the movement. The book stresses the heterogeneous nature of Peronism and traces the various ideological sources of its doctrine. It also analyzes Perón's machinations in order to maintain his leadership and eliminate any opposition within the movement.